Adoptive transfer of dendritic cells pulsed with Fasciola hepatica antigens and lipopolysaccharides confers protection against fasciolosis in mice - Falcón, Cristian Roberto (2012)
Dendritic cells (DCs) can function as adjuvants able to mediate protection against different pathogens. Given that successful vaccination against Fasciola hepatica is mostly related to the induction of Th1 responses, we studied the potential of DCs loaded with F. hepatica antigens and lipopolysaccharide (LPS) (which promote DCs maturation) as a vaccine against fasciolosis in BALB/c mice. However, only a semimature phenotype was achieved when DCs were simultaneously cultured with an F. hepatica total extract (TE) and LPS. The activation status of TE-loaded DCs was enhanced when these cells were treated with TE 90 minutes before being stimulated with LPS (TE90 DCs). More importantly, a single vaccination of mice with TE90 DCs stimulated a systemic Th1 response and conferred protection against hepatic damage induced by F. hepatica infection. Thus, TE90 DCs may prove to be a useful new tool for vaccination against F. hepatica. © The Author 2011. Published by Oxford University Press on behalf of the Infectious.